2001
DOI: 10.4049/jimmunol.167.11.6330
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of LIGHT on T Cells Leads to Lymphocyte Activation, Inflammation, and Tissue Destruction

Abstract: LIGHT, a member of the TNF family of cytokines (homologous to lymphotoxin, exhibits inducible expression and competes with HSV glycoprotein D for herpesvirus entry mediator, a receptor expressed on T cells), is induced on activated T cells and mediates costimulatory and antitumor activity in vitro. Relatively little information is available on the in vivo effects of LIGHT expression, particularly within the T cell compartment. In this work, we describe transgenic mice that express human LIGHT under the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
203
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(209 citation statements)
references
References 30 publications
4
203
0
Order By: Relevance
“…In addition, recent studies showed that LIGHT transgenic mice overexpressing LIGHT on T cells have enhanced immune response. 27,28 This result does not fit to the model in which LIGHT transduces negative signals into T cells, because if so, the LIGHT transgenic mice should have suppressed immune response instead. Lastly, there are about 4 to 5 TNF family members capable of transducing signals into cells, but none of them transduces a negative one.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, recent studies showed that LIGHT transgenic mice overexpressing LIGHT on T cells have enhanced immune response. 27,28 This result does not fit to the model in which LIGHT transduces negative signals into T cells, because if so, the LIGHT transgenic mice should have suppressed immune response instead. Lastly, there are about 4 to 5 TNF family members capable of transducing signals into cells, but none of them transduces a negative one.…”
Section: Discussionmentioning
confidence: 93%
“…One advantage of canarypox vector is its high-profiled safety, which has been demonstrated in both animal studies and clinical trials [5,9,29,48]. Another advantage of canarypox vector is that as a DNA virus that can only abortively infect mammalian cells, the target gene will be expressed transiently, which may be especially important for the expression of costimulatory molecules, such as CD40L, since long-term presence of costimulatory molecules might lead to autoimmunity or immunosuppression [49][50][51]. In our current study, we found no discernible signs of adverse effects of CD40L-expressing canarypox vector when used in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Since the expression of LIGHT (the HVEM ligand) on T cells is induced after activation, T cell activation through HVEM signaling may involve interaction of T cells with each other. Indeed, blockade of HVEM-LIGHT interactions inhibits proliferation of highly purified T cells in response to TCR stimulation (Shaikh et al, 2001). Thus, co-stimulation via HVEM depends on the presence of LIGHT on T cells (Morel et al, 2000;Scheu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%